2012
DOI: 10.1007/s10509-012-1086-6
|View full text |Cite
|
Sign up to set email alerts
|

The rms–flux relations in different branches in Cyg X-2

Abstract: In this paper, the rms-flux (root mean square-flux) relation along the Z-track of the bright Z-Source Cyg X-2 is analyzed using the observational data of Rossi X-ray Timing Explorer (RXTE). Three types of rms-flux relations, i.e. positive, negative, and 'arch'-like correlations are found in different branches. The rms is positively correlated with flux in normal branch (NB), but anti-correlated in the vertical horizontal branch (VHB). The rms-flux relation shows an 'arch'-like shape in the horizontal branch (H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For other broadband continuum components, which represent fast aperiodic variability, several models have been presented to explain this noise component, including the shot noise model, coronal flare model, and fluctuation propagation model (Terrell & James 1972;Nolan et al 1981;Belloni & Hasinger 1990;Mineshige et al 1994;Stern & Svensson 1996). Considering that the shot noise model predicts a stationary power spectrum and cannot produce a linear rms-flux relation for different timescales, it is not accepted to explain the broadband noise (Li et al 2012). Furthermore, Uttley (2004) showed that the rms-flux relation in the accreting millisecond pulsar SAX J1808.4-3658 is coupled with the 401 Hz pulsation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other broadband continuum components, which represent fast aperiodic variability, several models have been presented to explain this noise component, including the shot noise model, coronal flare model, and fluctuation propagation model (Terrell & James 1972;Nolan et al 1981;Belloni & Hasinger 1990;Mineshige et al 1994;Stern & Svensson 1996). Considering that the shot noise model predicts a stationary power spectrum and cannot produce a linear rms-flux relation for different timescales, it is not accepted to explain the broadband noise (Li et al 2012). Furthermore, Uttley (2004) showed that the rms-flux relation in the accreting millisecond pulsar SAX J1808.4-3658 is coupled with the 401 Hz pulsation.…”
Section: Introductionmentioning
confidence: 99%
“…This relation put a strict constrain on the origin of the rms-flux relation from magnetic caps of the neutron star, which means that the linear relation does not favor the coronal flare model for the X-ray variability. Up to now, the fluctuation propagation model is widely accepted because it naturally explains the rms-flux relation for different timescales, which is common in X-ray binaries (Uttley & McHardy 2001;Negoro & Mineshige 2002;Gleissner et al 2004;Uttley 2004;Uttley et al 2005;Li et al 2010Li et al , 2012. In the fluctuation propagation model (Lyubarskii 1997;Ingram & Done 2012;Ingram 2016;Mushtukov et al 2019), the broadband noise components are believed to break down at the local viscous frequency f visc ∝ 1/R 2 in a power spectrum with a Lorentzian shape ( ( ( )) )…”
Section: Introductionmentioning
confidence: 99%